PENTINGNYA DOKUMEN PERENCANAAN BAGI PENGEMBANGAN PESANTREN: Pendampingan Pengabdian Masyarakat Di Pondok Pesantren Salafiyah Syafi’iyah Sukorejo - Maskuri Maskuri (As-Sidanah, 2019)
Islamic boarding schools today require a planning document that describes a series of historical past as a philosophical basis for making changes in the future. The Sukorejo Pesantren strategic plan document that is being prepared through the team uses descriptive qualitative writing methods. Digging data sources with historical and phenomenological approaches. The purpose of the strategic plan is the realization of the strategic plan that will be used as a reference for organizers and managers of pesantren, both those who are undergoing leadership and future generations. The content is not only about history, but digs up-to-date information as a material for the characteristics and identity of pesantren which is maintained at all times. For this reason, the theoretical basis for preparing this strategic plan as an academic activity is the theory of change, progress, and change.